Nanomaterials in joining - Charitidis, Constantinos A. (Walter de Gruyter GmbH & Co., KG, 2016)
Joining techniques in engineering are of major importance. Innovations in the field of composites now allows design of nanomaterials with tailored properties. This book adresses techniques for similar and dissimilar joining, characterization of joint structures and damage prediction by simulation. A special focus is laid on welding of lightweight structures, which are of special economic interest for aeronautical and automotive applications.